THE INFLUENCE OF LIBRARY PERSONNEL SERVICE BEHAVIOR ON THE SATISFACTION OF MAN 2 DELI SERDANG SCHOOL LIBRARIANS - Damayanti, Ira; Sallima Nur Alaina Rambe; Nazla Sofi Adinda; Suci Nurhayati; Dea Nadhirah Mulyadi (CV. Asy Persada Quality, 2025)
This research aims to explore the relationship between library staff service behavior and user satisfaction at the MAN 2 Deli Serdang school using a qualitative approach. The research method involves selecting participants through purposive sampling techniques, collecting data through in-depth interviews and participant observation, thematic qualitative data analysis, and interpreting findings to describe the influence of service behavior on user satisfaction. The main findings highlight the importance of responsiveness to user needs, quality of information provided, friendliness, communication skills, and ability to solve problems as factors that influence user satisfaction. Practical implications of these findings include the importance of training and development of library staff to improve service quality and policy development to increase user satisfaction. This research makes an important contribution to the conceptual, practical, and theoretical understanding of the relationship between library staff service behavior and user satisfaction and emphasizes the importance of paying attention to these factors in improving library services in school environments.